ATTRIBUTES THAT ATTRACT THE GENERATION Y IN CHOOSING EMPLOYMENT: AN ANALYSIS FROM THE PERSPECTIVE OF SENIOR STUDENTS - Falaster, Christian; Ferreira, Manuel Portugal; Reis, Clóvis (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
The way which Generation Y perceives and values employment is different from the priorgenerations, requiring companies to adapt in order to recruit and retain this generation’sprofessionals. The main objective of this study is to analyze the attributes that attractGeneration Y employees in employment choice, a set of data was collected by questionnairepresented to students in final phases of undergraduate courses in Universidade Regional deBlumenau (FURB). The analyzed attributes were: work routine, personal interactions,professional development, economic benefits and social responsibility. The results reveal thatthis generation values all the approached aspects, but in different ways. This study hasimplications to practices regarding the improvement of ways to captivate and retain talent inthis generation.